2003
DOI: 10.1179/acb.2003.58.3.004
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Iron Deficiency Anaemia During Pregnancy in Belgium: Analysis of Routine Hospital Laboratory Data in Mons

Abstract: Anaemia during pregnancy is a common problem worldwide. In industrialised countries, it is still frequent in some groups of population. This study is based on the retrospective analysis of results of routine blood analysis performed on 15-44 years old women attending prenatal clinics (study group) or other outpatient clinics (non pregnant group) in a public hospital in Mons, Belgium from 1997 to 1999. In the non-pregnant group (2503 women), anaemia (haemoglobin < 12 g/dL) was present in 7.7% of the women. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 17 publications
3
6
1
1
Order By: Relevance
“…Over one‐third of all women (38%) in our study had ferritin levels < 12 μg/l during pregnancy or post‐partum. Other investigators have reported similar findings in 21.4–50% of women evaluated in the third trimester of pregnancy (15, 24–26). Compared to adults, adolescents had significantly lower levels of ferritin in the second and third samples and a higher rate of low ferritin throughout the study period ( p = 0.04).…”
Section: Discussionsupporting
confidence: 61%
“…Over one‐third of all women (38%) in our study had ferritin levels < 12 μg/l during pregnancy or post‐partum. Other investigators have reported similar findings in 21.4–50% of women evaluated in the third trimester of pregnancy (15, 24–26). Compared to adults, adolescents had significantly lower levels of ferritin in the second and third samples and a higher rate of low ferritin throughout the study period ( p = 0.04).…”
Section: Discussionsupporting
confidence: 61%
“…The prevalence of anemia varies both between and within countries. While the prevalence of anemia in pregnancy varies between 5% and 31% in developed nations (3)(4)(5), it may be as high as 90% in developing countries (6). In Russia, 20.8% of pregnant women are anemic according to the WHO database; however, no survey data from Russia were available, so this percentage was obtained using a regression equation with a low coefficient of determination (0.32), and thus should be accepted with caution (2).…”
Section: Introductionmentioning
confidence: 99%
“…Yapılan çalışmalarda (14,15,17,19,20,22) trimester ilerledikçe ortalama ferritin düzeylerinin düştüğü görülmektedir. Bizim çalışmamızda da aynı durum mevcuttu.…”
Section: Discussionunclassified